Construction and application of a multifunctional CHO cell platform utilizing Cre/lox and Dre/rox site-specific recombination systems - Zhang, Chen; Chang, Feng; Miao, Hui; Fu, Yunhui; Tong, Xikui; Feng, Yu; Zheng, Wenyun; Ma, Xingyuan (Frontiers in Bioengineering and Biotechnology, 2023)
During the development of traditional Chinese hamster ovary (CHO) cell lines, target genes randomly integrate into the genome upon entering the nucleus, resulting in unpredictable productivity of cell clones. The characterization and screening of high-yielding cell lines is a time-consuming and expensive process. Site-specific integration is recognized as an effective approach for overcoming random integration and improving production stability. We have designed a multifunctional expression cassette, called CDbox, which can be manipulated by the site-specific recombination systems Cre/lox and Dre/rox. The CDbox expression cassette was inserted at the Hipp11(H11) locus hotspot in the CHO-K1 genome using CRISPR/Cas9 technology, and a compliant CHO-CDbox cell platform was screened and obtained. The CHO-CDbox cell platform was transformed into a pool of EGFP-expressing cells using Cre/lox recombinase-mediated cassette exchange (RMCE) in only 2 weeks, and this expression remained stable for at least 75 generations without the need for drug stress. Subsequently, we used the Dre/rox system to directly eliminate the EGFP gene. In addition, two practical applications of the CHO-CDbox cell platform were presented. The first was the quick construction of the Pembrolizumab antibody stable expression strain, while the second was a protocol for the integration of surface-displayed and secreted antibodies on CHO cells. The previous research on site-specific integration of CHO cells has always focused on the single functionality of insertion of target genes. This newly developed CHO cell platform is expected to offer expanded applicability for protein production and gene function studies.